1993
DOI: 10.1111/j.1464-5491.1993.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Digital Pressure Measurements in Diabetic Neuropathic Foot Ulceration

Abstract: The diabetic neuropathic ulcer is typically slow to heal and recurrent. Macrovascular insufficiency is usually excluded as foot pulses are present and ankle:brachial pressure ratios are not decreased. These assessments cannot however exclude more distal vascular disease. Digital pressure measurements enable a reliable assessment of the distal peripheral vascular status to be made. The aim of this study was therefore to use toe pressures to assess the contribution of distal ischaemia in the pathogenesis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
14
2
Order By: Relevance
“…However, these ideas are in contradiction to findings from other studies (Stevens et al 1993, Netten et al 1996) that have demonstrated normal or elevated perfusion in nutritional capillaries.…”
Section: The Capillary Steal Theorycontrasting
confidence: 75%
See 4 more Smart Citations
“…However, these ideas are in contradiction to findings from other studies (Stevens et al 1993, Netten et al 1996) that have demonstrated normal or elevated perfusion in nutritional capillaries.…”
Section: The Capillary Steal Theorycontrasting
confidence: 75%
“…The patients perception of the applied stimuli provides an indication of the extent of sensory neuropathy (Brand 1990, Lavery et al 1998) and can be useful as part of the overall assessment of the risk of ulceration. The presence and extent of peripheral vascular disease can be assessed using Doppler ultrasound (Hill 1987, Williams et al 1993, plethysmography or laser Doppler flowmetry (Stevens et al 1993), to determine systolic pressure at the ankle or great toe respectively.…”
Section: Assessment Techniques For Complications Of the Diabetic Footmentioning
confidence: 99%
See 3 more Smart Citations